Feasibility and Safety of Intraoperative Electrochemotherapy in Locally Advanced Pancreatic Tumor: A Preliminary Experience. (September 2014) - Granata, V.; Fusco, R.; Piccirillo, M.; Palaia, R.; Lastoria, S.; Petrillo, A.; Izzo, F.
Electrochemotherapy is an effective treatment for various cutaneous tumors and could be translated into treatment of deep-seated tumors. With this aim, a prospective clinical phase I/II study was conducted to evaluate the feasibility and safety of intraoperative Electrochemotherapy (ECT) in locally advanced pancreatic adenocarcinoma: the preliminary results are reported in this study. The secondary endpoint was to assess treatment response in terms of morphological and functional criteria based on Magnetic Resonance Imaging. Eleven consecutive patients were enrolled in a clinical phase I/II study approved by the Ethics Committee of the National Cancer Institute G. Pascale Foundation - IRCCS of Naples. Electrochemotherapy with bleomycin was performed during open surgery. All patients underwent MR and CT scan, before and after ECT treatment, using morphological and functional imaging. RECIST criteria were used to evaluate ECT response on CT and MR images. Functional parameters were also used to evaluate ECT response on MR images. No acute (intraoperative) and/or postoperative serious adverse events related to electrochemotherapy were observed; no clinically significant electrocardiographic, hemodynamic, or serum biologic changes were noted. No clinically relevant elevation of amylase or lipase levels was observed and no bleeding or damage to surrounding viscera occurred. Electrochemotherapy of locally advanced pancreatic adenocarcinoma proved to be a feasible and safe treatment modality. Dynamic and diffusion MR imaging is more suitable to assess ECT treatment response than CT imaging and morphological MR alone, after one month of treatment.